"One swallow does not make a summer": discourses on punishment and decarceration policies in Costa Rica (2015-2017 / 2018-2020) - Marenco Silva, Eduardo (2022)
This article has the objective to analyze the discourse around punishment and decarceration policies on the administrations of the Ministry of Justice and Peace during the periods of 2015-2017 and 2018-2020. The discourses under study include the ones issued by politicians in power included in interviews, government plans and accountability speeches to the parliament. Is relevant the fact that the period under study is of two administrations of party continuity, where the prison system played a relevant role in the 2018 election and the decarceration policies were used against the ruling party for increasing insecurity in the country. To achieve the objective, the Critical Discourse Analysis methodology will be used, which will allow a deep understanding of the sociocultural problems from the discourses held by groups in power, which deepens the conditions of inequality and exclusion. It is concluded that, despite the continuity in power of a party with a supposedly progressive ideology, is possible to identify ruptures and important discontinuities between both governmental periods.